PEMANFAATAN FUZZY LOGIC DALAM MENILAI KUALITAS PELAYANAN KARYAWAN PADA DEPARTMENT STORE DI KOTA BATAM - Simatupang, Enjelina; Simanjuntak, Pastima (Computer Science and Industrial Engineering, 2020)
In realizing a prosperous and prosperous society the importance of the role of the developing economy, even in the era of free trade the company faces intense competition one of which is in department stores. The increasing intensity of competition and the number of competitors must always pay attention to the needs and desires of consumers and try to meet consumer expectations by providing more satisfying services than those carried out by competitors. Based on this research, it was found that many problems that often occur are the number of consumers who complain about the lack of satisfaction provided by the department store. This research explains about service, friendliness, and responsibility. In this study a decision support system was made using fuzzy logic. One application of decision support fuzzy logic is the Sugeno Fuzzy Inference System (FIS) Method. From the case examples conducted, it can be concluded that the Sugeno FIS method provides the right decision and is sufficient to assist the company in assessing the quality of employee services. Keywords: Services, Fuzzy Logic, FIS, Sugeno, Matlab